La muerte en el cotidiano de la graduación: Una mirada del alumno de medicina - Duarte, Anaísa Caparroz; de Almeida, Débora Vieira [UNESP]; Popim, Regina Célia [UNESP] (FapUNIFESP (SciELO), 2015)
This was a qualitative study in which the aim was to describe how fourth and sixthyear undergraduate students of human medicine deal with situations involving death. The theoretical-methodological reference framework of phenomenology was used. Both the fourth and the sixthyear students considered that death was a taboo subject, given that it was little discussed during the medical training. For the fourth-year students, the unpleasant feelings and sensations that accompany death in the context of care were mitigated by the teacher‟s presence and also by the expectation of learning. The sixthyear students revealed that experiencing the context of terminal illness and death enabled learning and incorporation of this topic into daily medical practice, despite the insecurities and difficulties presented. Hence, in addition to technical knowledge, skills in interpersonal relationships and emotional bonding are important for medical professionals in coping with the fatigue of clinical practice.
A morte no cotidiano da graduação: Um olhar do aluno de medicina
Death within the medical undergraduate routine: Students’ views
Keywords: Death; Medical Education; Medical students; Qualitative research